Propriedades estruturais e eletrônicas de nanotubos e nanofitas BxCyNz: um estudo por primeiros princípios - Gonçalves, Rebeca Dourado (2013)
In this work, we have performed first-principles calculations studie the energetic and stability and electronic structure of BxCyNz nanotubes and nanoribbons through the use of calculations based on Density Functional Theory implemented in the SIESTA code. Firstly we have considered zigzag and armchair carbon nanotubes. Then, we have substituted carbon atoms by boron and nitrogen atoms; therefore it is generated island of BN in carbon nanotube. It is found that BN island induces modifications on the electronic structure of such nanotubes, which can induced an opening or closing in the energy gap, depending on chirality, number of rings and diameter of these nanotubes. In addition, it is shown that the spin polarization of BC2N nanoribbons depends on both widths and configurations of such nanostructures. It is also seen that zigzag and armchair BC2N nanoribbons present a gap energy that strongly depends on width of nanoribbons. In addition, a magnetic behavior is observed for the zigzag structures for all widths considered as the armchair show no magnetization.